Image spaces. Digital visual media in the context of baroque mural painting in architecture - Piotr P. Drozdowicz (Images)
In the art of the 20th century, space became the basic material. Today, digital media and VR and AR technologies are used to cross the visual and space barriers, but always at the expense of experiencing reality. The spatial turn in culture results from the post-avant-garde ideas of art that cuts itself off from ancient art. Using the example of the fresco by Andrea del Pozzo from the Sant’Ignazio church in Rome, we will show analogies between baroque illusionist painting and digital visual media. It turns out that contemporary art arrives at the space issues that have been practiced in architecture and art since antiquity. The space created by painting illusion as a total work of art exhibits many features of contemporary art and the phenomena of VR and AR such as intermediality, immersion, interactivity. Spatial turn arguments can be used to enhance the potential of classic painting language in architecture.